Integrated process knowledge management system based on risk based process safety in petrochemical industries - Nur Izzati, Pakhor Anuar (2022)
Risk Based Process Safety (RBPS) guideline objective is to help the petrochemical industries to comply with Process Safety Management (PSM) standard. Outdated, scatted, and inaccessible process knowledge have been identified as significant causal factors of major accidents. Changing Process Knowledge Management (PKM) data can affect other elements, and changes in other elements also affect the reliability and accuracy of PKM elements. The shortcoming of study regarding PKM element interrelationship with other 19 Risk Based Process Safety (RBPS) has hindered the effectiveness of RBPS program. Besides that, lacking systematic system to implement the PKM program that integrates with others RBPS elements also delayed the improvement of process safety levels at the workplace. The research objectives of the study are to determine interrelationship of PKM element with other 19 RBPS elements, to develop a PKM flowchart and integrated flowchart based on RBPS guidelines, to develop integrated PKM system named Process Safety Knowledge Expert (PSKE) and to validate the developed PSKE via case studies, focus group discussion and System Usability Scale (SUS) study in Petrochemical industries. The research methodology used a qualitative, exploratory research design. The interrelationship of the PKM element with other 19 RBPS elements based on possible work activities used hierarchical structure (waterfall approach) and the interrelationship is presented into the mapping diagram and matrix table. A PKM flowchart, which consists of vital information and an implementation strategy to fulfil RBPS guideline requirements, was developed and integrated flowchart that highlights the interrelationship of PKM with other RBPS elements was developed after comprehensive literature review. Then, PSKE was developed using System Development Life Cycle (SDLC) approach. The front-end technology of PSKE used the Ionic framework apps development, meanwhile back-end technology used Firebase product by Google. Validation of the system involved three stages including case study at petrochemical Plant X, focus group discussion and System Usability Scale (SUS) study involving nine plant personnel (expert and key person) from HSSE and Operation department. PKM interrelationship matrix table has systematically confirmed that PKM has significant interrelationship with all of 19 RBPS elements. From the case study, PSKE allow the end-user to store, review, modify and update the data regarding hazardous chemicals, technology, and equipment information in real time. PSKE interfaces allow management to do a self-check audit and help the management to track the information. As a leading indicator, PSKE allows the user to review the overall status of the company compliance to the safety standard. In addition, PSKE allows management or employees to manage and review the PKM program, Process Hazard Analysis (PHA) and Asset Integrity and Reliability (AIAR) program simultaneously. For the SUS study, there are four statements scored 89% and all of 10 SUS statements got 0% for the scale ‘Disagree’ and ‘Strongly Disagree’. It can be concluded that PSKE received positive feedback in term of usability in petrochemical industries. Hopefully the system could help to increase the safety level at petrochemical plant and prevent major accidents simultaneously.